2017
DOI: 10.1097/aog.0000000000002269
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Care in the Postpartum Period

Abstract: One in 12 California women visited the emergency department in the first 90 days after postpartum discharge. Women at increased risk for postpartum emergency department use per our validated model (eg, low income, birth complications) may benefit from earlier scheduled postpartum visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 22 publications
5
33
0
Order By: Relevance
“…9,11,13 We also describe the incidence of unexpected office visits and emergency room visits, this last one being higher than previously reported after CD. 3 The etiologies associated with these outcomes are consistent with prior reports after CD, with the most common being infectious and hypertensive disorders. 14,15 Our study found that the vast majority were associated with infectious etiologies, while previous studies have reported lower infectious reason-for-visit percentages.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…9,11,13 We also describe the incidence of unexpected office visits and emergency room visits, this last one being higher than previously reported after CD. 3 The etiologies associated with these outcomes are consistent with prior reports after CD, with the most common being infectious and hypertensive disorders. 14,15 Our study found that the vast majority were associated with infectious etiologies, while previous studies have reported lower infectious reason-for-visit percentages.…”
Section: Discussionsupporting
confidence: 87%
“…A recent study showed that 8.3% of the patients who delivered in California visited the emergency department at least once during the first 3 months postpartum. 3 Almost one-third of women in the United States delivers via cesarean delivery (CD). 4 Compared with vaginal delivery, women undergoing a CD have a 5-to 10-fold increased risk of complications related to infections, 5 such as endometritis, wound complications, including disruption and infection.…”
mentioning
confidence: 99%
“…Total 5 to 12% of women have a hospital emergency room encounter within the initial 6-week postpartum period. [4][5][6][7] Based solely on discharge coding data, risk factors for emergency room visits include primiparity, young age, antepartum and delivery-related complications, hypertensive disorders of pregnancy, and cesarean delivery. 7,8 Women presenting to the emergency room most frequently complain of wound complications, fever, abdominal pain, and hypertension.…”
mentioning
confidence: 99%
“…However, it is known that women who underwent cesarean delivery frequently present to the ED postpartum. 6,8 It remains unclear if the ESI is useful for women who underwent vaginal delivery. Second, although our hospital protocol is for postpartum women to be evaluated in the ED instead of on the Labor and Delivery unit, 60 women were directly transferred to the labor and delivery unit or an inpatient floor either from the physician's office or from another hospitals.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…[3][4][5] Between 5 and 25% of postpartum women present to the ED at least one time after delivery. [6][7][8] Common causes of postpartum ED visits include urinary tract infection, hypertensive disorders, surgical site infections, and abdominal pain. [6][7][8] Although hypertensive disorders are the second most common indications for postpartum readmission, 6,8,9 blood pressure-a key vital sign-is not included in the ESI version 4 algorithm (►Fig.…”
mentioning
confidence: 99%